2007
DOI: 10.1152/ajpendo.00631.2006
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of carbonic anhydrase in rat pancreatic islets: enzymatic, secretory, metabolic, ionic, and electrical aspects

Abstract: Sener A, Jijakli H, Zahedi S, Courtois P, Yates AP, Meuris S, Best LC, Malaisse WJ. Possible role of carbonic anhydrase in rat pancreatic islets: enzymatic, secretory, metabolic, ionic, and electrical aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Since rapamycin treatment did not affect glucokinase activity in islets, the primary cause of reduced glucose oxidation by the treatment is not likely to be reduced the velocity of glycolysis. Indeed, in islets, glucose utilization is also reduced when glucose oxidation is decreased by respiratory chain inhibitors including site III inhibitor in our results and site VI inhibitor (Sener et al 2007), suggesting that reduced glucose oxidation may decrease glucose utilization. Since glucokinase is a unique hexokinase, which lacks product inhibition (Matschinsky 2002), accumulation of glucose-6-phosphate by mitochondrial metabolic inhibition may not participate in glycolysis inhibition.…”
Section: Discussionsupporting
confidence: 56%
“…Since rapamycin treatment did not affect glucokinase activity in islets, the primary cause of reduced glucose oxidation by the treatment is not likely to be reduced the velocity of glycolysis. Indeed, in islets, glucose utilization is also reduced when glucose oxidation is decreased by respiratory chain inhibitors including site III inhibitor in our results and site VI inhibitor (Sener et al 2007), suggesting that reduced glucose oxidation may decrease glucose utilization. Since glucokinase is a unique hexokinase, which lacks product inhibition (Matschinsky 2002), accumulation of glucose-6-phosphate by mitochondrial metabolic inhibition may not participate in glycolysis inhibition.…”
Section: Discussionsupporting
confidence: 56%
“…To our knowledge, there have been no previous reports of the effect of ZNS on blood glucose alone or in attenuating an acute drug-associated effect; however, studies with acetazolamide (a carbonic anhydrase inhibitor antiepileptic) in rats have shown that the integrity of carbonic anhydrase activity is required in order to allow a normal stimulation of insulin release by glucose (Sener et al, 2007). In addition, topiramate, a novel antiepileptic drug, with some similarities to ZNS, has been shown to attenuate OLZassociated weight gain (Liang et al, 2005;Wilkes et al, 2005a, b), decrease plasma glucose, and increase in vivo insulin sensitivity in adipocytes and skeletal muscle resulting from increases in adiponectin levels (Gustafson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, intracellular pH measurements and electrophysiological experiments, both carried out with dispersed rat islet cells, were performed as previously described [1,21]. The membrane potential of insulinproducing cells was monitored with the perforated configuration of the patch clamp technique.…”
Section: Functional Studiesmentioning
confidence: 99%
“…It was recently proposed that, in rat pancreatic islets, carbon dioxide is converted to a large extent to bicarbonate (HCO 3 -) [1]. However, the mechanism by which HCO 3 -leaves the islet cells remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%